Implikasi Keluarga Terhadap Pendidikan Perspektif Qur’ani - M.Pd., Mudrikah (Jurnal Munaqasyah, 2019)
Abstract: Education is a conscious and planned effort to create an atmosphere, learning process, and learning process so that students actively develop their potential to have religious spiritual strength, self-control, intelligence, noble character, and skills, which are needed by themselves, the nation and state. The National Education Objective is "developing capabilities and forming dignified national character and civilization in order to educate the nation's life, aiming at developing potential students to become faithful and devoted to God Almighty, noble, healthy, knowledgeable, capable, creative independent, and become a democratic and responsible citizen ". The success of the objectives of the National Education System is very much determined by three things, first the condition of the family, the two educational institutions, and the three conditions of society. Family as the first education (Tarbiyah al-Ula) for students, becomes the center of the next level of development. it means that family education is very instrumental in the survival and personal condition of the child. The family is the harmony of relationships that occur intensively and the fulfillment of the functions of needs both physically and psychologically which aims to develop the welfare of all family members in this case parents are examples or models for children. Parents have a very strong influence on this child can be seen from how parents leave the way of thinking to their children, parents are also the first mentor for children who have relationships and give deep affection, both positive and negative influences on children's personality development.